231k views
3 votes
Given f(x) and g(x) = k.f(x), use the graph to determine the value of k

User Hortensia
by
4.8k points

1 Answer

2 votes

Answer: The answer is -3

Explanation:

g(x)=kf(x)

g(-3)=kf(-3)

To solve this for k we will need to find the values for both g(-3) and f(-3).

g(-3) means we want the y that corresponds to x=-3 on the curve/line of g.

g(-3)=-3

f(-3) means we want the y that corresponds to x=-3 on the curve/line of f.

f(-3)=1

So our equation becomes:

g(-3)=kf(-3)

-3=k(1)

-3=k

So k=-3.

User Ptomli
by
5.7k points